Charge Carrier Mechanism in CdTe/ZnTe Core/Shell Nanocrystals for Photoelectrodes by Laser Ablation Method - M. Kadim, Akeel; M. Shareef, Amjed (Al-Nahrain Journal of Science, 2025)
Laser ablation in the UV-Vis absorption and emission spectra, as well as the duration increased and the emitted quantum efficiency increased., were used to synthesise and characterise of CdTe/ZnTe core/shell nanocrystals (NCs) or quantum dots (QDs). The dynamics via which carriers decrease and the distribution of excited state carriers were revealed by using ultrafast transient absorption spectroscopy to study the charge carrier process. A broad ground state bleach signal in the core/shell nanocrystals was seen in the transient absorption spectrum upon excitation by a laser pulse (Nd: YAG laser with 150 pulses and 600 mJ of power), which was consistent with the absorption spectra. These photoelectrodes were pre-sensitized by CdTe/ZnTe core/shell NCs that were deposited utilising an FTO/TPD/CdTe-ZnTe/PEDOT: PSS/Ag scaffold of a certain thickness on a transparent mesopous FTO (Fluoride tin oxide). According to PL measurements, the energygap (Eg) of CdTe/ZnTe core/shell NCs is around 2 and 2.5 eV for CdTe-core and ZnTe-shell respectively. A laser ablation-produced CdTe/ZnTe core/shell NCs improved the photoelectrodes' performance by improving the carrier's charge mobility and, therefore, recombination processes inside the NCs along with TPD and PEDOT: PSS polymer ions. A current-voltage (I-V) characteristic, in addition to lighting at 3V, verifies an ideal environment and formation. The surface trapping mechanism was eliminated because of the ZnTe shell's better surface passivation, which considerably slowed down the recombination in the core/shell nanocrystals.